1997
DOI: 10.1002/hep.510260718
|View full text |Cite
|
Sign up to set email alerts
|

Therapy of hepatitis C: Consensus interferon trials

Abstract: Chronic hepatitis C is an insidious disease associated with prior interferon therapy were more likely to have a serum HCV RNA end-of-retreatment and sustained response than significant morbidity and mortality. Currently, the only approved therapies for chronic hepatitis C are the alpha interfer-patients who were nonresponders to prior interferon therapy.After patients from the 3-mg CIFN cohort were excluded, the ons. Consensus interferon (CIFN) is a nonnatural, synthetic, recombinant type I interferon derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
4

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(45 citation statements)
references
References 18 publications
0
41
0
4
Order By: Relevance
“…A large study showed high rates of sustained response in relapsers re-treated with consensus interferon at the dosage of 15 µg for 24 or 48 weeks. 20 Recently, it was shown that combining interferon alfa with ribavirin induced a sustained response in 49% of relapsers as compared with 5% in patients receiving interferon alfa alone at the dosage of 3 MU for 24 weeks. 26 Future trials should define the respective indications of re-treatment with interferon alfa alone with a more intensive schedule or retreatment with the combination, taking into account tolerability, efficacy, and cost.…”
Section: Discussionmentioning
confidence: 99%
“…A large study showed high rates of sustained response in relapsers re-treated with consensus interferon at the dosage of 15 µg for 24 or 48 weeks. 20 Recently, it was shown that combining interferon alfa with ribavirin induced a sustained response in 49% of relapsers as compared with 5% in patients receiving interferon alfa alone at the dosage of 3 MU for 24 weeks. 26 Future trials should define the respective indications of re-treatment with interferon alfa alone with a more intensive schedule or retreatment with the combination, taking into account tolerability, efficacy, and cost.…”
Section: Discussionmentioning
confidence: 99%
“…The side effects of therapy (including fatigue, headache, anorexia, hair loss, depression, anxiety and other systemic, neurologic, psychologic, haematologic and autoimmune manifestations) are well documented and can be severe enough to warrant discontinuation of treatment, yet around 75 per cent of patients fail to respond. 5,10,[31][32] This, in combination with relatively strict criteria for access to treatment, means that the majority of individuals living with HCV will either not consider, or not be considered for, the available treatments.…”
Section: H Epatitis C Virus (Hcv) Infectionmentioning
confidence: 99%
“…Serum ALT is a surrogate marker for liver cell damage, which may be a consequence of the viral infection, but elevation of serum ALT can also be caused by fatty liver, fibrosis, cirrhosis, other causes of hepatitis, or even by agents used to treat viral hepatitis, such as IFNs. 8 Data from a large, randomized, double-blind study 9,10 in which patients were treated with either consensus IFN (CIFN) or IFN alfa-2b were used to compare biochemical, histologic, and virologic rates of response with IFN in nonfibrotic, fibrotic, and cirrhotic patients. Of the 704 patients with chronic HCV in this trial, 14% had bridging fibrosis and 14% had cirrhosis.…”
mentioning
confidence: 99%